LES ENJEUX DE LA TRADUCTION AUTOMATIQUE DES TEXTES POLITICO-JURIDIQUES. APPLICATION : L’ACCORD SUR LA DÉCLARATION DE PRINCIPE CONCERNANT LE GERD - Perihane Adel (Studii de gramatică contrastivă)
In this research work, we analyzed the problems of machine translation, via a contrastive study, of a political/legal document namely Declaration of principles on the Renaissance Dam (GERD). Our problem was to see to what extent the restitution of the meaning was correct and to evaluate the quality of the automatic translation for a pair of distant languages, namely the French language and the Arabic language, via the analysis of errors related to technical translation processes developed by Darbelnet et Vinay (1966), as well as grammatical, semantic, and lexical errors.